Effectiveness of whey protein supplementation on muscle strength and physical performance of older adults: a systematic review and meta-analysis of randomized clinical trials - Al-Rawhani, Alaa H.; Adznam, Siti Nur’Asyura; Abu Zaid, Zalina; Md. Yusop, Nor Baizura; M. Sallehuddin, Hakimah; Alshawsh, Mohammed A. (Churchill Livingstone, 2024)
Background: The efficacy of whey protein supplement (WPS) in improving muscle strength, physical performance, and body composition in older adults has been widely promoted. However, the results of randomized clinical trials in this regard have been inconsistent. We aimed to determine the impact of WPS, compared to a placebo, during or without training on muscle strength, physical function, and body composition in older adults. Methods: Randomized controlled trials were thoroughly searched using PubMed, EMBASE, the Cochrane Library Database, and Scopus databases up to June 2024. The analysis focused on key parameters such as handgrip strength (HS), leg press, knee extension, gait speed (GS), 6-min walking test (6MWT), Timed-up and go test (TUG), lean body mass (LBM), fat mass (FM), and appendicular skeletal muscle mass (ASM). A pooled effect size was calculated using a random-effects model based on standardized mean differences (SMD). Results: Thirty studies involving 2105 participants aged 60 and older met the inclusion criteria. The meta-analysis of 26 RCTs showed no significant positive effect of WPS on HS (n = 11, SMD: 0.18; 95% CI: −0.13, 0.49; I2 = 69%), 6MWT (n = 5, SMD: −0.08; 95%CI: −0.31, 0.16; I2 = 0%), GS test (n = 4, SMD: −0.08; 95%CI: −0.43, 0.28; I2 = 36%), TUG test (n = 9, SMD: 0.0, 95% CI -0.15, 0.14; I2 = 0%), LBM (n = 11, SMD: 0.02; 95%CI: −0.13, 0.17; I2 = 0%), FM (n = 15, SMD: −0.04; 95%CI: −0.18, 0.10; I2 = 0%). However, ASM significantly improved after WPS consumption but with high heterogeneity (n = 2, SMD: 0.39; 95%CI: 0.28, 0.51; I2 = 69%). In interventions incorporating RE, statistically significant positive effects of WPS on lower body strength were observed (n = 11, SMD: 0.25; 95%CI: 0.05, 0.45; I2 = 0%). Conclusion: The present meta-analysis indicates that WPS, when combined with resistance training (RT), can enhance lower body strength but does not seem to have a significant beneficial effect on handgrip strength, physical performance, or body composition. Further large-scale studies are necessary to confirm these findings and elucidate the potential benefits of WPS in this population.